Workshop on High Order Thinking Skills Mathematical Problems to Increase Teachers Teaching Abilities - Defri Ahmad; Syafriandi Syafriandi; Media Rosha (Fakultas MIPA Universitas Negeri Padang, 2020)
Abstract – To accomodate High Order Thinking Skills (HOTS) in classrom, we need to consider curricula, learning process, and assesment. Learning process and assesment have an essential requirement i.e. teacher’s ability. Government has done some activity to increase teacher’s ability to apply HOTS in classrom, but teachers need more. To keep their motivation and ability, teachers need a continue activity related to HOTS. Lecturer is an academic expert who teach in university level. In Indonesia, service to community is one of obligation for lecturer. Hence increasing teachers understanding about HOTS is one of lecturer’s duty. Training and workshops has been designed to rose teachers ability in creating HOTS problems and teaching using those problems. In this activity, teachers are studied about HOTS concept, the government policy about HOTS, solve some HOTS problem in National level test, and how to create HOTS base mathematical problems. For the next activity, teachers are asked to create some HOTS base mathematical problems, and design a learning trajectoty/ design to put their HOTS problem in learning process. Lastly, base on teacher’s satisfaction questionnaire, teachers are very happy to get this activity for the activity’s programme, mastery of topics, and teacher ‘s needs.